2018
DOI: 10.1080/09669582.2018.1478840
|View full text |Cite
|
Sign up to set email alerts
|

It’s so hot: predicting climate change effects on urban tourists’ time–space experience

Abstract: Progressive changes in mean annual temperatures are arguably the strongest evidence of ongoing climate change. In destinations with a Mediterranean climate, in contrast to the colder months, during summer, rising air temperatures are believed to inhibit tourist movements and activities, and consequently affect tourists' evaluation of and satisfaction with their experiences. To the best of our knowledge, no previous study has investigated the potential impact of climate change on tourists' time-space activity u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 121 publications
(175 reference statements)
1
14
0
1
Order By: Relevance
“…The data was input into SPSS v.23 and transformed and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with Smart PLS3 software (Caldeira & Kastenholz, 2018). PLS-SEM estimates partial model structures by combining principal components analysis with ordinary least squares regressions, it is usually used as an alternative to Covariance Based SEM (CB-SEM).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The data was input into SPSS v.23 and transformed and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with Smart PLS3 software (Caldeira & Kastenholz, 2018). PLS-SEM estimates partial model structures by combining principal components analysis with ordinary least squares regressions, it is usually used as an alternative to Covariance Based SEM (CB-SEM).…”
Section: Discussionmentioning
confidence: 99%
“…Hair et al (2014) suggested a two-step process to ensure the validity and reliability of PLS-SEM. First, evaluate the measurement (outer) model, and the relationship between the constructs and the associated indicators; then evaluate the structural (inner) model and analyze the hypothetical relationship between the constructs in the theoretical model (Caldeira & Kastenholz, 2018). Each of the various hypothetical relationships is associated with a corresponding causal path associated with each pair of structures in the structural model (Henseler et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The climate and weather quality of the destination perceived by tourists is the key factor affecting the overall travel satisfaction and loyalty of many tourists. During summer in Lisbon, Portugal, the maximum air temperature is found to have a significant negative effect on overall satisfaction (Caldeira and Kastenholz 2018). Perceived weather quality directly and indirectly affects tourist satisfaction and revisit intention and is correlated with the perceived quality of physical attributes and services (Kim et al 2017).…”
Section: Literature Review a Tourists' Perceptions Of Climate And Weathermentioning
confidence: 97%
“…Changes in weather patterns as a result of climate change will have widespread consequences for tourism demand (Hübner and Gössling 2012). Climate and weather affect tourists' satisfaction and intentions to revisit (Scott et al 2008;Kim et al 2017;Jeuring 2017;Caldeira and Kastenholz 2018). Curnock et al (2019) also analyzed the relationship among tourists' emotions, threat perception, and values related to their attitude toward climate change.…”
Section: Introductionmentioning
confidence: 99%